E-Governance in the Health Sector in India: A Review of the Current Scenario - Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
The Information and Communications Technology (ICT) has a huge potential of changing the landscape of service delivery across the globe. It acts as a catalyst for the speedy delivery of services. The Government of India is in the transition phase, moving from traditional paper mode to using Information and Communications Technology (ICT) in the governance process. The use of ICT in the governance process is called e-Governance. The Government of India has been increasingly focusing on the use of Information and Communications Technology (ICT) to overcome issues like red-tapism, lack of accountability and transparency in public services, lack of access to information, slow movement of files and other documents, ineffective delivery of public services etc. This is a concept paper based on secondary data collected from government websites and documents, various national and international Journals and private websites. The present paper discusses the concept of e-Governance, pillars of e-Governance, objectives of e-Governance, types of interaction in e-Governance, guiding principles for e-Governance and benefits of e-Governance. The paper presents a review of evolution of e-Governance in India. It gives a detailed account of e-Governance initiatives in India. The document lays specific emphasis on e-Governance initiatives in healthcare in India, both at the National and State level. Further, the key challenges related e-Governance in India are discussed. The paper also put forward some recommendations which may help in the implementation of e-Governance in the Indian context.
Keywords: 330; e-Governance; Information and Communication Technology; ICT; India